MOTIVASI INDONESIA MEMPERPANJANG INDONESIA – JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study intends to analyze Indonesia's motivation to extend the Indonesia-Japan Economic Partnership Agreement. Indonesia is involved in a bilateral trade agreement with Japan, known as the Indonesia-Japan Economic Partnership Agreement (IJEPA). The agreement was officially signed in 2008. IJEPA (Indonesia-Japan Economic Partnership Agreement) is a free trade agreement or (Free Trade Agreement) within the framework of a bilateral economic cooperation agreement that includes 3 main issues, namely, Liberalization, Facilitation, CooperationIn this study, the authors used library research and qualitative research methods. The analysis in this study uses the level of unit or country analysis, using the theory of international cooperation. The use of this theory is because the research discusses Indonesian cooperation agreements at the international level. The perspective in this study uses the perspective of Liberalism.Indonesia - Japan Economic Partnership Agreement is a bilateral cooperation in the economic sector and is expected to provide benefits to both countries through various schemes implemented. In general, this agreement has a broad scope with the aim of strengthening the economic partnership between the two countries.By seeing the benefits and potential of Indonesia in this agreement, Indonesia decided to continue to extend the IJEPA agreement after negotiating in the General Review with Japan.Keyword(s) : EPA, IJEPA, Motivation, Bilateral Agreement.